Drug-coated balloon in combination with bare metal stent strategy for de novo coronary artery disease: A PRISMA-compliant meta-analysis of randomized clinical trials. Issue 12 (March 2017) - Lu, Wenjie; Zhu, Yongjian; Han, Zhanying; Wang, Xi; Wang, Xule; Qiu, Chunguang
Abstract: Background: Studies examining the efficiency of drug-coated balloon (DCB) + bare metal stent (BMS) compared with stents alone for de novo lesions have reported inconsistent results. The present comprehensive meta-analysis of randomized controlled trials (RCTs) assessed and compared the clinical efficacy and safety of DCB + BMS with those of stents alone for de novo coronary artery disease. Methods: We formally searched electronic databases before September 2016 to identify potential studies. All RCTs were eligible for inclusion if they compared DCB + BMS with a control treatment (drug-eluting stent [DES] alone or BMS alone) in patients with de novo coronary artery disease. Results: Eleven RCTs with a total of 2196 patients met the inclusion criteria were included in our meta-analysis. Subgroup analysis indicated DCB plus BMS was associated with poorer outcomes when compared with DES alone in primary endpoint {(in-segment late lumen loss [LLL]: mean difference [MD], 0.19; 95% confidence interval [CI], 0.06–0.32; P  = 0.0042) and (major adverse cardiovascular events [MACEs]: risk ratio [RR], 1.88; 95% CI, 1.44–2.45; P  < 0.0001)}. However, DCB + BMS had nonsignificantly lower LLL than BMS alone (in-segment LLL: MD, −0.14; 95% CI, −0.33–0.04; P  = 0.24), and was more advantageous in reducing MACE incidence, with borderline significance (MACEs: RR, 0.67; 95% CI, 0.45–0.99; P  = 0.05). Conclusions: In summary, the present results do not favor the DCB + BMS strategy as an alternative therapeutic method to DES implantation for de novo coronary artery lesions in percutaneous coronary intervention (PCI). Additional well-designed large RCTs with long-follow-up periods are required to clarify the inconsistent results.